Biomedical coatings on magnesium alloys - a review - Hornberger, Helga; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Acta Biomaterialia, 2012)
This review comprehensively covers research carried out in the field of degradable coatings on Mg and Mg alloys for biomedical applications. Several coating methods are discussed, which can be divided, based on the specific processing techniques used, into conversion and deposition coatings. The literature review revealed that in most cases coatings increase the corrosion resistance of Mg and Mg alloys. The critical factors determining coating performance, such as corrosion rate, surface chemistry, adhesion and coating morphology, are identified and discussed. The analysis of the literature showed that many studies have focused on calcium phosphate coatings produced either using conversion or deposition methods which were developed for orthopaedic applications. However, the control of phases and the formation of cracks still appear unsatisfactory. More research and development is needed in the case of biodegradable organic based coatings to generate reproducible and relevant data. In addition to biocompatibility, the mechanical properties of the coatings are also relevant, and the development of appropriate methods to study the corrosion process in detail and in the long term remains an important area of research. © 2012 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.IW.LM.biomed
Keywords: Biodegradable materials; Coatings; Conversion; Deposition; Magnesium alloy

Characterization of electrophoretic chitosan coatings on stainless steel - Gebhardt, Franz; Seuß, Sigrid; Turhan, Can Metehan; Hornberger, Helga; Virtanen, Sannakaisa; Boccaccini, Aldo R. (Materials Letters, 2012)

Strengthening of dental adhesives via particle reinforcement - Belli, Renan; Kreppel, Stefan; Petschelt, Anselm; Hornberger, Helga; Boccaccini, Aldo R.; Lohbauer, Ulrich (Journal of the Mechanical Behavior of Biomedical Materials, 2014)
The bond between methacrylic polymer adhesives and dental restoratives is not perfect and may fail either in the short or in the long term. This study aims to evaluate the effects of particle incorporation in a self-etch model adhesive on mechanical and physical properties that are relevant during application and service. Filled adhesives containing 5, 10, 15 or 25. wt% glass fillers were compared to their unfilled counterpart in terms of water sorption and solubility; viscosity and dynamic viscosity during polymerization were recorded using rheological measurements and compared to FTIR analysis of the real-time degree of cure. Elastic modulus and ultimate tensile strength measurements were performed in uniaxial tension; the energy to fracture was used to calculate the fracture toughness of the adhesives. Finally, the experimental adhesives were applied on dentin substrate to test the bond strength using the microtensile test. Results showed that the incorporation of 5-10. wt% nanofiller to self-etching dental adhesives is efficient in accelerating the polymerization reaction and increasing the degree of cure without compromising the film viscosity for good wettability or water sorption and solubility. Fillers increased the elastic modulus, tensile strength and fracture toughness to a plateau between 5 and 15. wt% filler concentration, and despite the tendency to form agglomerations, active crack pinning/deflection toughening mechanisms have been observed. The bond strength between resin composite and dentin was also improved when adhesives with up to 10. wt% fillers were used, with no additional improvements with further packing. The use of fillers to reinforce dental adhesives may therefore be of great practical benefit by improving curing and mechanical properties. © 2014 Elsevier Ltd.
Keywords: Adhesives; Bond strength; Dentin; Elasticity; Nanoparticles